2010
DOI: 10.1002/jpln.200900004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus status of the soil on selenium availability

Abstract: Due to its importance for human and animal health, low bioavailability of selenium (Se) is of concern in large parts of the world. Among the factors determining Se availability is competition for binding sites by other anions. In order to evaluate the effect of different soil P status on Se availability from fertilizer, adsorption studies were conducted with soils ranging from low to very high available P as measured in ammonium lactate (P-AL) and addition of Se as either selenate or selenite. Generally seleni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…In contrast, a negative correlation was recorded between Se and N in barley (Ilbas et al 2012 ), which may be due to application of high Se doses resulting in Se toxicity. Similar to our observations, Eich-Greatorex et al ( 2010 ) observed high P uptake by Se application suggesting that Se interactions with phosphate are largely dependent on the source of Se as selenite uptake is not efficient in P-enriched medium (Dinh et al 2019 ). Contrary to our earlier report about no significant effect of Se on K content of wheat seeds (Nawaz et al 2015b ), an increased K content was recorded in mung bean seeds with S + Se treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, a negative correlation was recorded between Se and N in barley (Ilbas et al 2012 ), which may be due to application of high Se doses resulting in Se toxicity. Similar to our observations, Eich-Greatorex et al ( 2010 ) observed high P uptake by Se application suggesting that Se interactions with phosphate are largely dependent on the source of Se as selenite uptake is not efficient in P-enriched medium (Dinh et al 2019 ). Contrary to our earlier report about no significant effect of Se on K content of wheat seeds (Nawaz et al 2015b ), an increased K content was recorded in mung bean seeds with S + Se treatment.…”
Section: Discussionsupporting
confidence: 91%
“…This is caused by the strong complexation of phosphate in comparison to Se by hydrous ferric oxide surfaces [58], which is reflected by the respective complexation constants in the data base. This results in a very low selenium K d in fertilized soils which also has been reported by Eich-Greatorex et al [59]. The model predicts that at high phosphate concentrations, illite is the dominant sorbent, while at P < 0.1 mg/L, most of the selenium (>95%) is bound to hydrous oxide surfaces.…”
Section: Seleniumsupporting
confidence: 74%
“…The bioavailability of Se in soils is not only affected by soil properties such as pH, redox conditions, organic matter content, and synergy or antagonism of coexisting elements (Eich-Greatorex et al, 2010;Wang, Q. et al, 2016), but is also related to soil Se content and fraction (Wang et al, 2012). Activating stable Se in soil is a key process to increase the content of available Se and promote Se uptake by plants.…”
Section: Highlights Introductionmentioning
confidence: 99%